Bedside noninvasive monitoring of mechanically ventilated patients. Issue 1 (February 2021) - Via, Gabriele; Vasques, Francesco; Hussain, Arif; Barrett, Nicholas A.; Camporota, Luigi
Abstract : Purpose of review: Among noninvasive lung imaging techniques that can be employed at the bedside electrical impedance tomography (EIT) and lung ultrasound (LUS) can provide dynamic, repeatable data on the distribution regional lung ventilation and response to therapeutic manoeuvres. In this review, we will provide an overview on the rationale, basic functioning and most common applications of EIT and Point of Care Ultrasound (PoCUS, mainly but not limited to LUS) in the management of mechanically ventilated patients. Recent findings: The use of EIT in clinical practice is supported by several studies demonstrating good correlation between impedance tomography data and other validated methods of assessing lung aeration during mechanical ventilation. Similarly, LUS also correlates with chest computed tomography in assessing lung aeration, its changes and several pathological conditions, with superiority over other techniques. Other PoCUS applications have shown to effectively complement the LUS ultrasound assessment of the mechanically ventilated patient. Summary: Bedside techniques – such as EIT and PoCUS – are becoming standards of the care for mechanically ventilated patients to monitor the changes in lung aeration, ventilation and perfusion in response to treatment and to assess weaning from mechanical ventilation.